Prognozowanie sytuacji gospodarczej przedsiębiorstw przemysłowych - Kowalewski, Grzegorz (Forecasting activity of situation of economic industrial enterprise, 2005)
Researching of quality of forecast formulated is purpose of article by directors of industrial enterprises in Poland. In weak situation of propriety of forecast try (taste) to find (to be placed) it reason. Two meters ex post employ for estimate of accuracy of forecast fast: Theil and for differences divergence. Article is based on empirical research. Results of business conditio surveys are base of estimate of forecast.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonometria (15); 2005; nr 1096, s. 261-274